2021
DOI: 10.31004/cendekia.v5i1.451
|View full text |Cite
|
Sign up to set email alerts
|

Studi Eksploratif Tentang Pemahaman Guru Terhadap Kerangka Kerja TPACK Dalam Pembelajaran Matematika di Tengah Pandemi di SMA Kota Jambi

Abstract: Pandemi COVID-19 seakan “memaksa” guru dan siswa untuk melakukan modernisasi dalam pembelajaran. Di zaman modernisasi seperti sekarang, manusia sangat bergantung pada teknologi, terlebih di saat pandemi. Semua tingkat sekolah di Kota Jambi yang melakukan pembelajaran secara daring (online). Tak terkecuali dalam proses pembelajaran matematika di tingkat SMA. Berdasarkan latar belakang masalah yang telah diuraikan, maka rumusan masalah penelitian ini adalah bagaimana pemahaman guru terhadap kerangka kerja TPACK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…One of the innovations is the application of TPACK in the learning process, for example (Pahlevi et al, 2021) in his research which states that TPACK training for teachers can help them integrate the use of technology, teaching and teaching materials in learning well. Almost the same thing was also stated by (Pahlevi et al, 2021;Wijayanto, 2017;Jannah & Rahman, 2021;Aditama & Pratiwi, 2021;Mutiani et al, 2021;Najibah et al, 2022;Munajib et al, 2021) where the researchers agreed that TPACK as a role model for learning that is oriented towards change and guidance for the 21st century in responding to the era of knowledge.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…One of the innovations is the application of TPACK in the learning process, for example (Pahlevi et al, 2021) in his research which states that TPACK training for teachers can help them integrate the use of technology, teaching and teaching materials in learning well. Almost the same thing was also stated by (Pahlevi et al, 2021;Wijayanto, 2017;Jannah & Rahman, 2021;Aditama & Pratiwi, 2021;Mutiani et al, 2021;Najibah et al, 2022;Munajib et al, 2021) where the researchers agreed that TPACK as a role model for learning that is oriented towards change and guidance for the 21st century in responding to the era of knowledge.…”
Section: Introductionmentioning
confidence: 60%
“…However, not a few researchers about TPACK state that the mastery of TPACK by educators is quite good. For example (Munajib et al, 2021) which states that the understanding of mathematics teachers at Jambi City High School towards the TPACK framework in online mathematics learning during the COVID-19 pandemic is quite good, as well as (Munajib et al, 2021) which states that the understanding of mathematics teachers at Jambi City High School towards the TPACK framework in online mathematics learning during the COVID-19 pandemic is sufficient good. Other findings regarding the TPACK model in learning state that the implementation of learning based on the TPACK framework has been carried out properly (Maharani et al, 2021;Fajero et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers lack understanding and knowledge of educational tools. It was also found that most respondents had sufficient expertise, and 22% had a super understanding (Apriani et al, 2021;Fasha & Hibana, 2023;Munajib et al, 2021).…”
Section: Teacher's Understanding Of Tpck In Javanese Language Learningmentioning
confidence: 95%
“…Technology Pedagogy and Content Knowledge (TPACK) yakni pengetahuan tentang cara menggunakan berbagai teknologi untuk mengajar sehingga dapat memfasilitasi pengetahuan tentang konten subjek tertentu. Dalam implementasinya menurut Munajib (2021), ditemukan beberapa kendala pada guruguru senior yang memiliki usia lanjut yang mana sebagian sulit memahami teknologi namun memiliki jam terbang mengajar yang tinggi. Untuk mengatasi hal tersebut maka harus dilakukan seminar atau webinar agar pemahaman akan teknologi semakin meningkat.…”
Section: Implementasi Tpack Guru Dalam Pembelajaran Pada Masa Covid-19unclassified